Contemporary views on drug discovery techniques - Aleksandrova, K. V.; Vasylyev, D. A.; Makoyid, O. B.; Mikhalchenko, E. K.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович; Макоїд, Ольга Борисівна; Михальченко, Євген Костянтинович (Дніпро : Організація наукових медичних досліджень «Salutem», 2020)
The last decade of study and growth in pharmacophores design has fashioned revolutionary results. The present successes are based on improvements in several crucial parameters: (I) medicinal chemistry energies have developed much-improved modifications of existing medicines, in order to produce the high-affinity molecules; (II) the knowledge uprising of the roles and biological mechanisms of action of various enzymes; and (III) the translational drug discovery part. The latter relays to many branches of bioinformatics like computer algorithms, biochemical analyses, better pharmacokinetics/pharmacodynamics (PK/PD) models, ADME models, and wide variety of toxicology investigations.